1907 Or. Laws 292, ch. 149, § 1. - (:unkn) unknown (General Publisher, 1907)
If any person shall break and enter any building in the night time with intent to commit a crime therein, and shall in the commission of or attempt to commit such crime, use or attempt to use nitro-glycerine, dynamite, gunpowder or other high explosive, such person shall be deemed guilty of burglary with explosives, and upon conviction thereof shall be punished by imprisonment in the penitentiary for not less than five years nor more than forty years.
--
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME